2005
DOI: 10.1080/07420520500263276
|View full text |Cite
|
Sign up to set email alerts
|

An Olfactory Stimulus Modifies Nighttime Sleep in Young Men and Women

Abstract: Aromatherapy is an anecdotal method for modifying sleep and mood. However, whether olfactory exposure to essential oils affects night-time objective sleep remains untested. Previous studies also demonstrate superior olfactory abilities in women. Therefore, this study investigated the effects of an olfactory stimulus on subsequent sleep and assessed gender differences in such effects. Thirty-one young healthy sleepers (16 men and 15 women, aged 18 to 30 yr, mean+/-SD, 20.5+/-2.4 yr) completed 3 consecutive over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(78 citation statements)
references
References 78 publications
4
70
0
4
Order By: Relevance
“…It has been demonstrated that lavender aromatics can improve sleep in the elderly [12] and infants [13]. Furthermore, exposure to lavender odors during sleep results in increased duration of deep slow-wave stage sleep [14]. A therapeutic effect that is closely related to sleep is anxiety reduction, and many studies have evaluated the anxiolytic potential of lavender essential oil.…”
Section: Studies In Human Subjectsmentioning
confidence: 99%
“…It has been demonstrated that lavender aromatics can improve sleep in the elderly [12] and infants [13]. Furthermore, exposure to lavender odors during sleep results in increased duration of deep slow-wave stage sleep [14]. A therapeutic effect that is closely related to sleep is anxiety reduction, and many studies have evaluated the anxiolytic potential of lavender essential oil.…”
Section: Studies In Human Subjectsmentioning
confidence: 99%
“…Numerous studies have shown that odors influence mood (Knasko 1992(Knasko , 1995Schiffman et al 1995a,b;Lehrner et al 2005), performance in cognitive tasks as well as person and object evaluation (Rotton 1983) congruently with their valence (see also Ehrlichman & Bastone 1992;Herz 2009). In addition, behavioral and physiological approaches revealed that odors can alter an individual's arousal by inducing relaxation or excitation (e.g., Torii et al 1988;Bensafi et al 2002a;Heuberger et al 2004;Goel et al 2005). Although sensory affect is increasingly included in sensory testing by the food and fragrance industry, and gains importance in product development, theoretical and methodological supports are only in the early stages of development.…”
mentioning
confidence: 99%
“…It also helps to reduce insomnia, increase deep sleep with slow waves in people, and leaves one more alert during the day (13). The results of the Goel study showed that aromatherapy can improve sleep quality and its essence helps to fall asleep faster, increasing the 2nd stage of sleep, and decreased rapid eye movement (14).…”
Section: Introductionmentioning
confidence: 88%